Γ – semigroup generated by a semigroup. (April 2020) - Sumanto, Y D; Aziz, A; Solikhin,; Hariyanto, S
Abstract: In Γ – semigroup S, the element of Γ maybe a binary operation in S . Every element of any semigroup S can define a binary operation in S. A collection of binary operations defined of the element of S generates Γ – semigroup S .